Nutritional status of under-five children in rural Bangladesh - Liton Chandra Sen; Md. Sabbir Ahmed; Abu Shoeb Md. Touhiduzzaman; Soumitra Mandal; AH Towfique Ahmed; Sanjit Kumar Das; Rama Saha (Intelektual Pustaka Media Utama, 2020)
A cross-sectional study was carried out in Dumki Upazila of Patuakhali district in Bangladesh to assess the prevalence of stunting, wasting and underweight among the under-five children. Anthropometric measurements were taken from all children, aged 0-59 months in the studied area using wooden height board and digital weight machine. We used WHO Anthro software for analyzing the z scores of the children. A total of 4409 (2296 boys and 2113 girls) under five children were counted for anthropometric analysis. Regarding the Height-for-age Z-score (HAZ), the study revealed that the prevalence of stunting was 27.10% (95% CI: 25.8-28.5) of the children while 7.80% (95% CI: 7-8.6) were severe stunting. By assessing the Weight-for-height Z-score (WHZ), the study showed that 11.20% (95% CI: 10.3-12.1) were wasting whereas 3% (95% CI 2.5-3.5) were severe wasting. According to Weight-for-age Z-score (WAZ), about 18.20% (95% CI: 17-19.3) were underweight and 4.1% (95% CI: 3.5-4.7) were underweight. The findings of the study show that prevalence of stunting is very high. Focusing on childhood stunting is a high priority, and there should be comprehensive efforts to increase the overall nutritional status of the under-five children in this area.